Surgical Managements for Traumatic Avulsed Scalp: 10 year Experiences in 14 Case at Prapokkloa Regional Hospital - Kriangsak Sirirak (Siriraj Medical Journal, 2004)
Traumatic avulsed scalp is an uncommon and serious injury. The best management for the sake of functional and cosmetic purpose of this type of injury is replacing the avulsed scalp with its own tissues. Objectives : Alternative surgical managements for avulsed scalp. Study design : Retrospective design. Materials & methods : From 1995 to 2004, there were 14 cases admitted with traumatic avulsed scalp, 7 men and 7 women. Among these patients nine of them had partial loss their scalp, while five cases had totally lost theirs. Results : Among these 14 patients, 5 cases were classified as women with totally avulsed scalps, caused by contact with agricultural machines. One case died from multiple traumas. Four cases survived; 2 cases for replantation (one case successful replantation has good hair growth, and all others are baldness. 9 cases, partially avulsed scalp, were 7 men, and 2 women. 6-scalp flap had good result with normal hair growth. 1-scalp flap with skin graft and 2-skin graft had baldness. Conclusion : Microsurgical replantation is the treatment of choice for avulsed scalp. However, if replantation is unavailable, one stage reconstruction with well-vascularized tissue must be done. As avulsed scalp is a serious injury, prevention is very important.